Asymmetric drop coalescence launches fungal ballistospores with directionality. Issue 132 (26th July 2017) - Liu, Fangjie; Chavez, Roger L.; Patek, S. N.; Pringle, Anne; Feng, James J.; Chen, Chuan-Hua
Abstract : Thousands of fungal species use surface energy to power the launch of their ballistospores. The surface energy is released when a spherical Buller's drop at the spore's hilar appendix merges with a flattened drop on the adaxial side of the spore. The launching mechanism is primarily understood in terms of energetic models, and crucial features such as launching directionality are unexplained. Integrating experiments and simulations, we advance a mechanistic model based on the capillary–inertial coalescence between the Buller's drop and the adaxial drop, a pair that is asymmetric in size, shape and relative position. The asymmetric coalescence is surprisingly effective and robust, producing a launching momentum governed by the Buller's drop and a launching direction along the adaxial plane of the spore. These key functions of momentum generation and directional control are elucidated by numerical simulations, demonstrated on spore-mimicking particles, and corroborated by published ballistospore kinematics. Our work places the morphological and kinematic diversity of ballistospores into a general mechanical framework, and points to a generic catapulting mechanism of colloidal particles with implications for both biology and engineering.